Carbon-sequestration high-crack-resistance concrete and preparation method thereof

By adding specific raw materials to concrete and combining carbon sequestration technology, the problems of high carbon emissions and insufficient crack resistance in traditional concrete production are solved, and efficient carbon emission reduction and crack resistance improvement are achieved, which is suitable for a variety of construction and engineering applications.

CN119638305APending Publication Date: 2025-03-18NINGBO GUANGTIAN BAIFA NEW MATERIALS CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411596437.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-11
Publication Date
2025-03-18

AI Technical Summary

Technical Problem

The high carbon emissions in traditional concrete production process lead to an increase in environmental pollution and carbon footprint. The existing technology is difficult to effectively reduce carbon emissions and improve the crack resistance of concrete.

Method used

By adding fly ash, magnesium expansion agent, organic amine compounds, alkali agents and carbon sequestration materials to the concrete, and combining carbon sequestration technology, the crack resistance and carbon emission reduction effect of concrete is synergistically improved.

Benefits of technology

It significantly improves the crack resistance of concrete, achieves efficient carbon emission reduction, and produces a high crack resistance concrete that is both environmentally friendly and has good mechanical properties, suitable for various construction and engineering fields.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005127030710000081
    Figure BDA0005127030710000081
  • Figure BDA0005127030710000091
    Figure BDA0005127030710000091
Patent Text Reader

Abstract

The invention belongs to the technical field of concrete materials, and relates to carbon-sequestration high-crack-resistance concrete and a preparation method thereof. The carbon-sequestration high-crack-resistance concrete is processed from the following raw materials in parts by weight: 450 to 600 parts of cement, 10 to 100 parts of fly ash, 600 to 800 parts of river sand, 1000 to 1200 parts of gravel, 100 to 200 parts of water, 0.1 to 10 parts of an additive, 0.5 to 10 parts of an alkaline agent, 0.1 to 5 parts of an organic amine compound, 30 to 80 parts of a magnesium expanding agent, 1 to 20 parts of fiber and 1 to 10 parts of a carbon-sequestration material. According to the carbon-sequestration high-crack-resistance concrete provided by the invention, multiple raw materials are preferably selected, and through the synergistic effect of the raw materials, the application effect of a carbon sequestration technology in the concrete is remarkably enhanced, and through the synergistic effect of the multiple components, the volume of the concrete generates a micro-expansion effect, so that the crack resistance of the concrete is improved; the carbon emission can be reduced, and the requirement of sustainable development is met.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of concrete materials and relates to a carbon-fixing high-crack-resistance concrete and a preparation method thereof. Background Art

[0002] Concrete plays a vital role in building and infrastructure construction due to its wide availability and excellent properties. It is a composite material formed by aggregates being bonded together by a cementitious material. The advantages of concrete include the abundance of raw materials, relatively low cost, simple production process, high compressive strength, good durability and a wide range of strength grades. These advantages make concrete the material of choice in various civil engineering projects.

[0003] However, the production and use of traditional concrete also brings a series of environmental problems, especially the carbon emission problems related to cement. A large amount of carbon dioxide is released during the production of cement. It is estimated that about 511 kg of carbon dioxide is produced for every ton of Portland cement produced. This makes the cement industry one of the important sources of carbon emissions in the world, especially in China, where the carbon emissions of the cement industry account for about 15% of the country's total emissions. This high carbon footprint not only exacerbates climate change, but also has a negative impact on the ecological environment.

[0004] In view of this, the development of low-carbon concrete technology has become particularly important. The research on low-carbon concrete aims to reduce the carbon footprint of building materials while maintaining or improving the performance of concrete. Therefore, it is urgent to explore carbon solidification technology to improve the crack resistance of concrete and reduce carbon emissions, provide scientific basis and technical support for the realization of more environmentally friendly and durable concrete materials, and promote the sustainable development of the concrete industry. Summary of the invention

[0005] The present invention aims at the deficiencies of concrete materials in the prior art and provides a low-carbon high-cracking resistance concrete and a preparation method thereof.

[0006] One object of the present invention is achieved by the following technical solutions:

[0007] A carbon-fixing high-cracking-resistant concrete is processed from the following raw materials in parts by weight: 450-600 parts of cement, 10-100 parts of fly ash, 600-800 parts of river sand, 1000-1200 parts of crushed stone, 100-200 parts of water, 0.1-10 parts of admixture, 0.5-10 parts of alkali agent, 0.1-5 parts of organic amine compound, 30-80 parts of magnesium expansion agent, 1-20 parts of fiber, and 1-10 parts of carbon-fixing material.

[0008] The present invention provides a carbon-fixing high crack-resistant concrete, which optimizes a variety of raw materials and significantly enhances the application effect of carbon fixation technology in concrete through the synergistic effect between these raw materials. This multi-component synergistic effect not only effectively fixes CO2 and achieves an efficient carbon emission reduction effect, but also significantly improves the crack resistance of concrete. Through the reasonable proportioning and optimized combination of the above raw materials, the present invention can produce a high crack-resistant concrete that is both environmentally friendly and has good mechanical properties. It is suitable for various construction and engineering fields, especially in applications that require high-strength and long-life structures. In addition, this concrete can also reduce the impact on the environment during the construction process to a certain extent, meeting the requirements of sustainable development.

[0009] Preferably, the cement has a specific surface area of ​​300 to 500 m 2 / kg, 7d strength is 25-30MPa, 28d strength is 50-60MPa, initial setting time is 200-250min, and final setting time is 260-300min. Among them, 7d strength refers to the compressive strength that cement can reach in 7 days; 28d strength refers to the compressive strength that cement can reach in 28 days; initial setting time refers to the time from the beginning of stirring with water to the time when the cement paste begins to lose plasticity and cannot be easily pressed with fingers; final setting time refers to the time from the beginning of stirring with water to the time when the cement paste completely loses plasticity, becomes hard and can no longer be processed.

[0010] Preferably, the fly ash is Class F Grade I fly ash, with a loss on ignition of 3-4wt%, a fineness of 8.0-10.0wt%, and a water requirement ratio of 90-95wt%. Among them, fly ash is divided into Class F (low-calcium fly ash) and Class C (high-calcium fly ash). Class F fly ash mainly comes from the combustion process of anthracite or lignite; fly ash is divided into Class I, Class II and Class III according to quality grade, and Class I fly ash has the highest quality requirements; loss on ignition refers to the percentage of mass lost by fly ash after burning at high temperature. The lower the loss on ignition, the less unburned carbon and other volatile substances in the fly ash, and the smaller the impact on the performance of concrete; fineness refers to the percentage of fly ash passing through a 45μm square hole sieve in the total mass. The higher the fineness, the finer the fly ash particles, which can better fill the gaps when mixed with cement and improve the density of concrete; water demand ratio refers to the ratio of the amount of water required for concrete mixed with fly ash compared with the benchmark concrete under the condition of maintaining the same fluidity. The lower the value, the smaller the impact of fly ash on the workability of concrete, and it may even reduce the amount of water used.

[0011] Preferably, the river sand has a fineness modulus of 4.0-4.5 and a mud content of 1.5-2.0 wt %. The fineness modulus is an indicator of the coarseness of the sand; the mud content refers to the percentage of impurities such as clay and silt contained in the sand. Too high a mud content will affect the strength and durability of the concrete, because these impurities will absorb moisture and reduce the effective water-cement ratio of the cement paste, thereby affecting the workability of the concrete and the performance after hardening.

[0012] Preferably, the crushing value of the crushed stone is 7.0-8.0%, and the content of needle-like particles is 5.0-6.0%. The crushing value is an indicator to measure the crushing resistance of the crushed stone. The lower the crushing value, the higher the strength of the crushed stone and the better the compression resistance; needle-like particles refer to those particles with an aspect ratio greater than 3:1 (i.e., the ratio of length to width is greater than 3). Such particles are prone to cause uneven structure in concrete, affecting the workability and mechanical properties of concrete.

[0013] Preferably, the crushed stone is a mixture of small stones with a particle size of 6 to 11 mm and large stones with a particle size of 17 to 26 mm, and the mixing ratio is 1: (1 to 6), and more preferably 1: (3 to 6).

[0014] Preferably, the admixture is a polycarboxylic acid high-performance slow-setting water-reducing agent. Polycarboxylic acid high-performance slow-setting water-reducing agent is a highly efficient concrete admixture, which has multiple functions, including water reduction, slow setting and improvement of concrete workability. This type of water-reducing agent is usually based on the chemical structure of polycarboxylates, which can significantly reduce the amount of water in concrete, while prolonging the setting time of concrete, so that the concrete maintains good plasticity and fluidity for a long time.

[0015] Preferably, the alkali agent includes one or more of sodium carbonate, sodium hydroxide and potassium hydroxide, and more preferably sodium carbonate.

[0016] The present invention adds an alkali agent to the concrete raw materials, which can be used to activate the chemical substances in the fly ash in the raw materials, and can generate calcium silicate hydrate (CSH) gel and other stable mineral phases through alkali excitation, thereby improving the strength and durability of the concrete; further preferred sodium carbonate can be decomposed to produce carbon dioxide and sodium oxide, which can play an alkali excitation role, and react with CO2 to generate sodium bicarbonate, which is further converted into calcium carbonate, accelerating the carbon fixation process of concrete, thereby promoting the carbon fixation effect, and the generated calcium carbonate can play a certain role in compensating for shrinkage, reducing cracks, increasing density, and improving crack resistance.

[0017] Preferably, the organic amine compound is an amino acid, including one or more of lysine, glycine, arginine, histidine, aspartic acid, and serine.

[0018] The present invention introduces amino acid components into concrete raw materials and combines carbon fixation technology, which can react with CO2 to generate stable compounds such as carbonates, thereby promoting the carbon fixation effect. At the same time, the presence of amino acids will also increase the reactivity of fly ash and magnesium expansion agent component materials, thereby improving the performance of concrete. In addition, the amino acids can be used as toughening agents to increase the toughness of concrete and reduce the occurrence of cracks; promote more uniform microstructure distribution, thereby improving the overall performance of concrete.

[0019] Preferably, the magnesium oxide content in the magnesium expansion agent is 70-80wt%, the limiting expansion rate at 25°C is 0.01-0.02%, and the limiting expansion rate at 50°C is 0.04-0.05%.

[0020] Preferably, the carbon-fixing high crack-resistant concrete comprises the following fibers in parts by weight: 1 to 10 parts of basalt chopped fibers and 0.1 to 10 parts of polypropylene fibers.

[0021] Preferably, the density of the basalt chopped fibers is 2.5 to 3.0 g / cm 3 , diameter is 12-17μm, length is 15-20mm, and tensile strength is 1050-1100MPa.

[0022] Preferably, the polypropylene fiber has a breaking strength of 630-650 MPa and an initial modulus of 5.0-5.5 GPa.

[0023] Preferably, the carbon-fixing material is MgO and / or CaO.

[0024] More preferably, the carbon-fixing material is a compound of MgO and CaO, and the compounding mass ratio is (1-3): (1-3).

[0025] Another object of the present invention is achieved by the following technical solutions:

[0026] A method for preparing carbon-fixing high crack-resistant concrete, the preparation method comprising the following steps:

[0027] Mix cement, fly ash, river sand and crushed stone evenly, add water, admixture, alkali agent, organic amine compound, magnesium expansion agent and carbon-fixing material and continue to stir; then add basalt chopped fiber and polypropylene fiber and stir evenly; cast the mixed slurry into shape and then cure it until it is completely hardened to obtain a concrete blank; finally, perform carbon-fixing treatment to obtain a finished carbon-fixing high-cracking-resistant concrete.

[0028] Preferably, the curing conditions include an ambient temperature of 18-22° C. and an ambient humidity of ≥95%.

[0029] Preferably, the ambient temperature of the carbon fixation treatment is 20-25° C. and the humidity is 45-80%.

[0030] Preferably, the carbon fixation device needs to be checked for tightness before the carbon fixation treatment, including the following steps: opening the main valve, exhaust valve and vacuum valve of the carbon fixation device, and when the internal air pressure of the carbon fixation device is ≤-0.7 bar, closing the exhaust valve and vacuum valve in sequence to ensure that the airtightness of the carbon fixation device meets the requirements.

[0031] Preferably, the CO2 concentration is greater than 99%, and the gas pressure in the carbon fixation device is 0.1 to 1 bar.

[0032] Compared with the prior art, the present invention has the following beneficial effects:

[0033] 1. The carbon-fixing and highly crack-resistant concrete provided by the present invention adopts a variety of raw materials and additives to produce a synergistic effect, and combines carbon-fixing technology to effectively improve the carbon-fixing effect of concrete, causing the volume of concrete to expand slightly, thereby improving the crack resistance of concrete and effectively reducing its carbon emissions, thereby achieving a more sustainable building material solution.

[0034] 2. The carbon-fixing and highly crack-resistant concrete provided by the present invention has cement, fly ash, river sand and crushed stone as main components to provide the basic structure and strength of the concrete; polycarboxylic acid high-performance slow-setting water-reducing agent is added as an admixture to adjust the working performance of the concrete, making it have better fluidity and operability; the magnesium expansion agent compensates for the volume change of the concrete caused by drying shrinkage and reduces the risk of cracking; basalt chopped fibers and polypropylene fibers enhance the toughness of the concrete and prevent the formation and development of early cracks.

[0035] 3. The carbon-fixing and highly crack-resistant concrete provided by the present invention significantly improves the carbon-fixing effect of concrete by introducing multiple components and combining with advanced carbon-fixing technology, thereby improving the anti-cracking performance of concrete and enhancing its carbon emission reduction effect. Among them, alkali agents, organic amine compounds and carbon-fixing materials can generate stable compounds such as carbonates during carbon-fixing treatment, accelerate the carbon-fixing process of concrete, promote the carbon-fixing effect, and make the concrete produce a volume micro-expansion effect, thereby improving its anti-cracking performance; the introduced organic amine compounds use amino acids, and their presence will also increase the reaction activity of other component materials; the introduced carbon-fixing materials use Mg and Ca-based oxides, which strengthen the carbon absorption and carbon-fixing performance of concrete. At the same time, because it can further promote the formation of carbonate products, it enhances the volume micro-expansion of concrete and the anti-cracking performance of high concrete.

[0036] 4. The carbon-fixing and highly crack-resistant concrete provided by the present invention not only effectively fixes CO2 and reduces the greenhouse gas content in the atmosphere through the synergistic effect of multiple components and the combination of carbon-fixing technology, but also significantly improves the crack resistance of concrete. The present invention has successfully developed a highly crack-resistant concrete that is both environmentally friendly and has good mechanical properties. It is suitable for various construction and engineering fields, especially in applications that require high-strength and long-life structures. In addition, this concrete can also reduce the impact on the environment during construction to a certain extent, meeting the requirements of sustainable development. DETAILED DESCRIPTION

[0037] The technical solution of the present invention is further described below in conjunction with specific embodiments. It should be understood that the specific embodiments described herein are only used to illustrate the present invention and are not intended to limit the scope of the present invention. In addition, it should be understood that after reading the content taught by the present invention, those skilled in the art can make various changes or modifications to the present invention, and these equivalent forms also fall within the scope defined by the claims attached to this application.

[0038] The raw material information in the following examples and comparative examples is as follows:

[0039] (1) Cement: P·O 42.5 cement with a specific surface area of ​​400m 2 / kg, 7d strength 26.1MPa, 28d strength 51.2MPa, initial setting time 210min, final setting time 275min, in line with GB 175-2017 requirements;

[0040] (2) Fly ash: Class F Grade I fly ash, with a loss on ignition of 3.9%, fineness of 9.0%, and water requirement ratio of 93%, in compliance with the requirements of GB / T 1596-2017;

[0041] (3) River sand, fineness modulus 4.1, mud content 1.8%, in line with the requirements of JTG / T 3650-2020;

[0042] (4) Crushed stone, with a crushing value of 7.8% and a needle-like content of 5.6%, which meets the requirements of JTG / T 3650-2020 and is a mixture of small stones with a particle size of 6 to 11 mm and large stones with a particle size of 17 to 26 mm;

[0043] (5) Admixture: polycarboxylic acid high-performance retarding water reducer (Ningbo Zhongshuike composite high-efficiency water reducer) is used, which meets the requirements of GB 8076-2008;

[0044] (6) Magnesium expansion agent, with a magnesium oxide content of 75wt%, a limited expansion rate of 0.016% at 25°C, and a limited expansion rate of 0.046% at 50°C, which meets the requirements of CBMF 19-2017;

[0045] (7) Basalt chopped fiber, density 2.65g / cm 3 , diameter 15μm, length 18mm, tensile strength ≥1050MPa;

[0046] (8) Polypropylene fiber, breaking strength 635 MPa, initial modulus 5.2 GPa, in line with the requirements of GB / T21120-2007.

[0047] Example 1

[0048] The carbon-fixing high crack-resistant concrete of this embodiment is made from the following raw materials in parts by weight: 500 parts of cement, 48 parts of fly ash, 714 parts of river sand, 241 parts of small stones, 788 parts of large stones, 161 parts of water, 10 parts of polycarboxylic acid high-performance slow-setting water-reducing agent, 8 parts of sodium carbonate, 2 parts of lysine, 53 parts of magnesium expansion agent, 8 parts of basalt chopped fibers, 6 parts of polypropylene fibers, and 5.14 parts of carbon-fixing materials (MgO and CaO are compounded in a mass ratio of 1:1).

[0049] The preparation method of the carbon-fixing high crack-resistant concrete in this embodiment comprises the following steps:

[0050] (1) Add cement, fly ash, river sand and gravel into a mixer and mix them evenly, then add water, polycarboxylic acid high-performance slow-setting water-reducing agent, sodium carbonate, lysine, magnesium expansion agent and carbon-fixing material and continue to stir; then add basalt chopped fibers and polypropylene fibers and stir evenly;

[0051] (2) After the mixed slurry is cast into shape, it is cured in an environment with a temperature of 20° C. and a humidity of 97% until it is completely hardened to obtain a concrete blank;

[0052] (3) Carry out carbon fixation treatment in an environment with a temperature of 22°C and a humidity of 60%: open the main valve, exhaust valve and vacuum valve of the carbon fixation device in sequence, and when the internal air pressure of the carbon fixation device is -0.7 bar, close the exhaust valve and vacuum valve in sequence to ensure that the airtightness of the carbon fixation device meets the requirements; then put the concrete blank in; introduce CO2 (concentration>99%) and adjust the air pressure in the carbon fixation device to 0.5 bar; after carbon fixation is completed, close the air inlet valve, open the exhaust valve and vacuum valve of the carbon fixation device in sequence, and close all valves until the air pressure in the carbon fixation device is 0, and take out the carbon-fixed concrete from the device to obtain carbon-fixed high-cracking-resistant concrete.

[0053] Example 2

[0054] The difference between this embodiment and embodiment 1 is that the raw material ratio in embodiment 1 is replaced by the raw material ratio in this embodiment, and the preparation method is the same as that in embodiment 1.

[0055] The carbon-fixing high crack-resistant concrete of this embodiment is made from the following raw materials in parts by weight: 460 parts of cement, 40 parts of fly ash, 670 parts of river sand, 183 parts of small stones, 917 parts of large stones, 160 parts of water, 8 parts of polycarboxylic acid high-performance slow-setting water-reducing agent, 5 parts of sodium carbonate, 1 part of arginine, 42 parts of magnesium expansion agent, 7 parts of basalt chopped fibers, 5 parts of polypropylene fibers, and 5.2 parts of carbon-fixing materials (CaO).

[0056] Comparative Example 1

[0057] The difference between this comparative example and Example 1 is that the raw material ratio in Example 1 is replaced by the raw material ratio in this comparative example, and the preparation method is the same as Example 1.

[0058] The concrete of this comparative example is made from the following raw materials in parts by weight: 412 parts of cement, 134 parts of fly ash, 810 parts of river sand, 145 parts of small stones, 914 parts of large stones, 160 parts of water, 12 parts of polycarboxylic acid high-performance slow-setting water-reducing agent, 10 parts of sodium carbonate, 1 part of lysine, 20 parts of magnesium expansion agent, 15 parts of basalt chopped fibers, 15 parts of polypropylene fibers, and 5.01 parts of carbon-fixing material (MgO and CaO are compounded in a mass ratio of 1:1).

[0059] Comparative Example 2

[0060] The difference between this comparative example and Example 1 is that sodium carbonate is not added to the concrete raw materials, and the rest is the same as Example 1.

[0061] Comparative Example 3

[0062] The difference between this comparative example and Example 1 is that no organic amine compound is added to the concrete raw materials, and the rest is the same as Example 1.

[0063] Comparative Example 4

[0064] The difference between this comparative example and Example 1 is that no carbon-fixing material is added to the concrete raw materials, and the rest is the same as Example 1.

[0065] Comparative Example 5

[0066] The difference between this comparative example and Example 1 is that the carbon-fixing material in the concrete raw material is NaO, and the rest is the same as Example 1.

[0067] Comparative Example 6

[0068] The difference between this comparative example and Example 1 is that no carbon fixation treatment is performed in the preparation method, and the rest is the same as Example 1.

[0069] Comparative Example 7

[0070] The difference between this comparative example and Example 1 is that sodium carbonate, organic amine compounds and carbon-fixing materials are not added to the concrete raw materials, and carbon-fixing treatment is not performed in the preparation method. The rest is the same as Example 1.

[0071] The concrete of the above-mentioned embodiment and comparative example were subjected to relevant performance tests, and the specific test results are shown in Table 1.

[0072] Table 1 Performance test results of embodiments and comparative examples

[0073]

[0074]

[0075] As shown in Table 1, it can be seen from Examples 1 to 2 that the concrete material prepared using the raw materials within the scope of the technical solution of the present invention is helpful to improve the mechanical properties of concrete and has excellent strength; and the incorporation of carbon fixation technology into concrete can cause it to expand in volume, compensate for the volume shrinkage of the concrete itself, and help reduce the risk of cracking. According to the volume expansion rate data, it can be seen that the present invention applies carbon fixation technology to concrete to significantly improve the crack resistance of concrete, and the effect becomes more obvious as the age of concrete increases. It is sufficient to prove that the carbon-fixed high-crack-resistant concrete of the present invention can achieve carbon emission reduction and improve the quality and performance of concrete through the optimization of raw materials and the combination of carbon fixation technology, and has broad application prospects.

[0076] It can be seen from Comparative Examples 1 to 7 that the concrete materials prepared without using the technical solution of the present invention have different degrees of reduction in concrete strength and crack resistance. Comparative Examples 1 to 6 do not use the preferred raw material formula and proportion of the present invention, and the strength grade and volume expansion rate cannot reach the level of the embodiment, so the crack resistance of the concrete cannot be improved. In Comparative Example 7, carbon fixation technology and carbon fixation materials are not used, and the mechanical properties and volume expansion rate of the prepared concrete have dropped significantly, and the improvement of the crack resistance of the concrete cannot be achieved.

[0077] The various aspects, embodiments, and features of the present invention should be considered to be illustrative in all aspects and not limiting of the present invention, the scope of which is defined solely by the claims. Other embodiments, modifications, and uses will be apparent to those skilled in the art without departing from the spirit and scope of the claimed invention.

[0078] In the preparation method of the present invention, the order of each step is not limited to the order listed. For those skilled in the art, without creative work, the order of each step is also within the protection scope of the present invention. In addition, two or more steps or actions can be performed simultaneously.

[0079] Finally, it should be noted that the specific embodiments described herein are merely examples of the present invention, and are not intended to limit the implementation methods of the present invention. A person skilled in the art of the present invention may make various modifications or supplements to the specific embodiments described, or replace them in a similar manner. It is not necessary and impossible to provide all examples of all implementation methods here. However, these obvious changes or modifications derived from the essential spirit of the present invention still fall within the scope of protection of the present invention, and interpreting them as any additional limitation is contrary to the spirit of the present invention.

Claims

1. A carbon-fixing high crack-resistant concrete, characterized in that: The carbon-fixing high-cracking-resistant concrete is processed from the following raw materials in parts by weight: 450-600 parts of cement, 10-100 parts of fly ash, 600-800 parts of river sand, 1000-1200 parts of crushed stone, 100-200 parts of water, 0.1-10 parts of admixture, 0.5-10 parts of alkali agent, 0.1-5 parts of organic amine compound, 30-80 parts of magnesium expansion agent, 1-20 parts of fiber, and 1-10 parts of carbon-fixing material.

2. The carbon-fixing high crack-resistant concrete according to claim 1, characterized in that: The alkaline agent includes one or more of sodium carbonate, sodium hydroxide and potassium hydroxide.

3. The carbon-fixing and highly crack-resistant concrete according to claim 1, characterized in that: The organic amine compound is amino acid, including one or more of lysine, glycine, arginine, histidine, aspartic acid and serine.

4. The carbon-fixing high crack-resistant concrete according to claim 1, characterized in that: The carbon fixing material is MgO and / or CaO.

5. The carbon-fixing and highly crack-resistant concrete according to claim 1, characterized in that: The specific surface area of ​​the cement is 300 to 500 m 2 / kg, 7d strength is 25-30MPa, 28d strength is 50-60MPa, initial setting time is 200-250min, and final setting time is 260-300min; And / or, the fly ash is Class F Grade I fly ash, with a loss on ignition of 3-4wt%, a fineness of 8.0-10.0wt%, and a water requirement ratio of 90-95wt%; And / or, the river sand has a fineness modulus of 4.0 to 4.5 and a mud content of 1.5 to 2.0 wt%.

6. The carbon-fixing and highly crack-resistant concrete according to claim 1, characterized in that: The carbon-fixing high crack-resistant concrete according to claim 1 is characterized in that the crushing value of the crushed stone is 7.0-8.0%, and the content of needle-like particles is 5.0-6.0%; The crushed stone is a mixture of small stones with a particle size of 6 to 11 mm and large stones with a particle size of 17 to 26 mm, and the mixing ratio is 1: (1 to 6).

7. The carbon-fixing and highly crack-resistant concrete according to claim 1, characterized in that: The admixture is a polycarboxylic acid high-performance retarding water reducer; And / or, the magnesium oxide content in the magnesium expansion agent is 70-80wt%, the limiting expansion rate at 25°C is 0.01-0.02%, and the limiting expansion rate at 50°C is 0.04-0.05%.

8. The carbon-fixing and highly crack-resistant concrete according to claim 1, characterized in that: The carbon-fixing high crack-resistant concrete comprises the following fibers in parts by weight: 1 to 10 parts of basalt chopped fibers and 0.1 to 10 parts of polypropylene fibers; The density of the basalt chopped fibers is 2.5 to 3.0 g / cm 3 , diameter is 12-17 μm, length is 15-20 mm, and tensile strength is 1050-1100 MPa; The polypropylene fiber has a breaking strength of 630-650 MPa and an initial modulus of 5.0-5.5 GPa.

9. A method for preparing a carbon-fixing high crack-resistant concrete according to any one of claims 1 to 8, characterized in that: The preparation method comprises the following steps: Mix cement, fly ash, river sand and crushed stone evenly, add water, admixture, alkali agent, organic amine compound, magnesium expansion agent and carbon-fixing material and continue to stir; then add basalt chopped fiber and polypropylene fiber and stir evenly; cast the mixed slurry into shape and then cure it until it is completely hardened to obtain a concrete blank; finally, perform carbon-fixing treatment to obtain a finished carbon-fixing high-cracking-resistant concrete.

10. The preparation method according to claim 9, characterized in that: The curing conditions include an ambient temperature of 18-22° C. and an ambient humidity of ≥95%. And / or, the carbon fixation treatment environment temperature is 20-25°C and the humidity is 45-80%; And / or, before the carbon fixation treatment, the carbon fixation device needs to be checked for tightness, including the following steps: open the main valve, exhaust valve, and vacuum valve of the carbon fixation device, and when the internal air pressure of the carbon fixation device is ≤-0.7 bar, close the exhaust valve and vacuum valve in sequence to ensure that the airtightness of the carbon fixation device meets the requirements.